Correlation between Nurse Motivation and the Quality of Nursing Care Documentation - Anita Lufianti; Keristiyani Keristiyani (Inspirasi Foundation, 2023)
Introduction: Nursing documentation is evidence of nurses' recording and reporting in providing accurate and complete written health services. Documenting nursing care is quite important. However, there are still many incomplete nursing care documentations written by nurses. The factor that encourages nurses to carry out nursing documentation is the nurse's motivation and supported by rewards from the hospital as appreciation for the nurse's performance. Objective: The purpose of this study was determine the Correlation between Nurse Motivation and the Quality of Nursing Care Documentation. Method: This research is a quantitative study with a correlation study and a cross sectional design. The sampling technique used was random sampling with 66 respondents at RSUD Dr. R. Soedjati Somodiarjo Purwodadi. The data were analyzed by using the chi-square statistical test (X2) and a correlation strength test was carried out using Spearman's (r). Results: Based on the chi-square statistical test (X2), the p value is 0.000. As the results show <0.05, it means that Ha is accepted and Ho is rejected. Then a correlation strength test carried out by using Spearman’s (r) reveals a correlation coefficient or r = 0.086, indicating that there is a strong positive correlation between nurses’ motivation and the quality of nursing care process documentation at RSUD Dr. R. Soedjati Somodiarjo Purwodadi. Conclusion: The results of the study indicate that there is a positive correlation between nurses’ motivation and the quality of the nursing care process documentation at RSUD Dr. R. Soedjati Somodiarjo Purwodadi.